Special Applications of Photogrammetry - Carneiro da Silva, Daniel (IntechOpen, 2012)
Photogrammetry is widely accepted as one of the best surveying methods to acquire tridimensional data without direct contact with the object, but its high operational costs in equipment and personnel somewhat limit its application in mapping. However, with the development of digital photogrammetry in the 1990's, it was possible to introduce automated processes and reduce the personnel costs. In the following years, the cost of computer hardware, digital cameras and positioning sensors has been lowering, making photogrammetry more accessible to other engineering fields, such as architecture, archeology and health fields. This book shows the results of the work of researchers from different professional backgrounds, which evaluate the uses of photogrammetry, including issues of the data, processing, as well as the solutions developed for some surveying types that can be extended to many applications.